Comparing Methods for the Estimation of CO2 Storage Capacity in Saline Aquifers in Germany: Regional Aquifer Based vs. Structural Trap Based Assessments. (July 2017) - Knopf, S.; May, F.
Abstract: Estimates of CO2 storage capacity are often based on regional aquifer assessments. In Germany however, capacity estimations have been based on the assessment of individual traps also. For method comparison, a new nationwide capacity assessment was performed, using the 'regional aquifer based' method. This assessment yields a capacity of 20.4 – 115.3 Gt, which is higher than earlier 'trap based' estimates. Results for the Middle Buntsandstein in the North German Basin yield 6.6 – 41.8 Gt for the regional- and 4.8 – 9.7 Gt of storage capacity for the trap based method, with a less distinct range of uncertainty for the latter.